Thermodynamic functions for solubility of 3-nitro-o-toluic acid in nine organic solvents from T = (283.15 to 318.15) K and apparent thermodynamic properties of solutions. (July 2017) - Li, Xinbao; Wang, Mingju; Du, Cunbin; Cong, Yang; Zhao, Hongkun
Graphical abstract: Highlights: Solubilities of 3-nitro- o -toluic acid in nine organic solvents were determined. The solubilities were correlated by using four thermodynamic models. The mixing properties of solution were computed based on Wilson model. Abstract: Separation of 3-nitro- o -toluic acid from its isomeric mixtures has essential significance in industry. In this work, by using isothermal saturation method, the solid-liquid equilibrium for 3-nitro- o -toluic acid in nine organic solvents (acetonitrile, methanol, ethanol, n -propanol, isopropanol, ethyl acetate, acetone, 1, 4-dioxane and 2-butanone) were obtained experimentally within a temperature range from (283.15 to 318.15) K under atmosphere pressure of 101.2 kPa, and the solubility values of 3-nitro- o -toluic acid in these solvents were determined by a high-performance liquid chromatography. Within the studied temperature range, the mole fraction solubility of 3-nitro- o -toluic acid in selected organic solvents increased with increasing temperature. Except for ethyl acetate, the descending order of the mole fraction solubility values were as follow: 1, 4-dioxane > acetone > 2-butanone > methanol > ethanol > isopropanol >  n -propanol > acetonitrile. The solubility values determined for 3-nitro- o -toluic acid in the selected solvents were correlated and back calculated with the modified Apelblat equation, λh equation, Wilson model and NRTL model. The largest values of RAD and RMSD obtained with the four models were 0.67% and 4.02 × 10 −4, respectively. In general, the four thermodynamic models were all acceptable for describing the solubility behaviour of 3-nitro- o -toluic acid in these solvents. In addition, the apparent mixing Gibbs energy, mixing enthalpy, mixing entropy, activity coefficient at infinitesimal concentration and reduced excess enthalpy were calculated. The acquired solubility data and thermodynamic studies would be very important in optimizing the separation process of 3-nitro- o -toluic acid from its isomeric mixtures.